SOME SOCIO-ECONOMIC PROBLEMS INHIBITING ECONOMIC DEVELOPMENT IN THE ARAB AGRARIAN SECTOR - الأسدي فوزي (Dirasat in Economics and Business, 1977)
The Arab countries are fortunate enough in possessing certain resources which are essential for their economic progress; such as the termendous oil resources, the fabulous oil-reveues in scarce currencies, in addition to vast agricultural lands and abundant water resources (in some countries) as well as a mild climate suitable for agricultural production throughout the year. Yet the Arab countries are still branded as "under-developed" countries-particularly in the agrarian sector.